Systematische und historische Bemerkungen zum – bleibenden – kritischen Anspruch von Hegels spekulativer Logik - Schäfer, Gregor (Revista Eletrônica Estudos Hegelianos, 2022)
The essay argues for the critical potential inherent in Hegel’s speculative-logical thinking against a dominant strand of reception that separates the conception of objective spirit from the systematic speculative-logical framework. The argument hereby puts forward (i) that such receptions, ultimately, integrate their understanding of Hegel into the existing world and accommodate it to its hegemony; (ii) that an interpretation focusing on the entire speculative-logical framework, on the contrary, implies a critique of the existing world by articulating, within this world, a crisis and the possibility of action and change out of this very crisis
Keywords: Absolute Spirit; Crisis; Emancipation; Objective Spirit; Reception of Hegel; Speculative Logic; System; World History